Model Pengaruh Harga International Terhadap Penjualan Ekspor Pupuk Urea Pada Pt Xyz Menggunakan Marketing Mix Strategy - Tegar Garin Widodo; Dwi Sukma Donoriyanto (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
PT XYZ is one of the largest fertilizer companies in Indonesia. One of the company's goals is to become a competitive producer of fertilizers and other chemical products that are in high demand among consumers. To achieve this, the company needs a marketing strategy to boost sales, compete with both domestic and international rivals, and address the fluctuations in sales volume. Therefore, the company has opted to use multiple linear regression as a reference to assess whether sales prices and international prices have an impact on sales volume. Additionally, the marketing mix, or the combination of marketing elements, will be crucial in achieving the company's objectives. In the execution of marketing activities, every company strives to establish marketing strategies and target its market. This marketing strategy revolves around the marketing mix. The research findings indicate that sales prices and international prices do not have a significant impact on sales volume, possibly due to the presence of other variables such as the company's location, product promotion, and other factors influencing the results.